A review of the environmental parameters necessary for an optimal sleep environment. (15th March 2018) - Caddick, Zachary A.; Gregory, Kevin; Arsintescu, Lucia; Flynn-Evans, Erin E.
Abstract: An appropriate sleep environment is critical to achieve adequate quality and quantity of sleep. General sleep hygiene recommendations suggest that individuals should maintain a cool, dark, quiet sleep environment. Our goal was to conduct a review of the evidence surrounding the optimal characteristics for the sleep environment in the categories of noise, temperature, lighting, and air quality in order to provide specific recommendations for each of these components. We found that all forms of noise in the sleep environment should be reduced to below 35 dB. The optimal ambient temperature varies based on humidity and the bedding microclimate, ranging between 17 and 28 °C at 40–60% relative humidity. Complete darkness is optimal for sleep and blue light should be avoided during the sleep opportunity. Sea level air quality, with ventilation is optimal for sleep and supplemental oxygen is a useful countermeasure for improving sleep quality at altitude. Architectural design that incorporates these elements into bedroom design may improve sleep quality among inhabitants of such environments.